The influence of culture conditions on the physico-chemical properties of exopolysaccharide etapolana - Pirog, Tatiana; Korzh, Yuliya; Shevchuk, Tetiana (My University, 2009)
The physicochemical properties of the complex exopolysaccharide ethapolan (EPS) produced by Acinetobacter sp. 12S during growth on media with various C/N ratios and different concentrations of mineral components and phosphate buffer were studied. Irrespective of the cultivation conditions, the concentrations of carbohydrates (38–44%) and pyruvic acid (3.2–3.7%) in the total EPS, as well as in the acylated (AP) and nonacylated (NAP) polysaccharides obtained from them, were practically the same. The EPS, AP, and NAP were also identical in their monosaccharide composition: the molar ratio of glucose, mannose, galactose, and rhamnose was 3 : 2 : 1 : 1. The polysaccharides contained different concentrations of mineral salts (6–28%), uronic acid (3.7–22.0%), and fatty acids (5.8–15.4%); they also differed in the ratio of acetylated and nonacetylated polysaccharides. Due to the differences in the chemical composition and molecular mass (500 kDa – 1.5 MDa), the viscosities of the EPS solutions (in the presence of 0.1 M KCl, in the H+–form, and in Cu2+–glycine system) were different as well. The mechanisms responsible for changes in the physicochemical properties of the total EPS, AP, and NAP synthesized on various media are discussed.
Keywords: exopolysaccharide; екзополісахарид; біосинтез полісахаридів; biopolymers; polysaccharide biosynthesis; біополімери; культивування; кафедра біотехнології і мікробіології